Authorized Redundant Check Support in a Hybrid Cloud Environment - Durgadevi, .; Shreedhara N, Hegde; Zuriani Hayati, Abdullah (INTI International University, 2024)
A hybrid cloud is made up of public and private clouds connected by standardized or proprietary technologies to provide data and application mobility. The deduplication with uneven privileges issue in cloud computing is addressed efficiently. an architecture for a hybrid cloud that employs both public and private clouds, with the data owners only using the public cloud for storage and the private cloud for data administration. To make data management in cloud computing scalable, duplication has lately become a commonly employed method. Deduplication reduces the amount of bandwidth you need, speeds up data transfers, and keeps your need for cloud storage to a minimum. To enable authorized duplicate checks in hybrid cloud architecture, the proposed system comprises a variety of new deduplication structures. Data confidentiality was protected before outsourcing by employing the convergent encryption method. A system authorized to use deduplication supports differential authorization duplicate checks. In the authorized duplication check approach, testbed tests are carried out using a prototype as proof of concept.